Legal Inequality in Determining Child Custody Rights After Divorce: A Gender-Based Normative Analysis (Lembaga Contrarius Indonesia, 2026)
This study examines legal inequality in determining child custody (hadhanah) after divorce in Indonesia. Although the Marriage Law, the Compilation of Islamic Law (KHI), and the Child Protection Law provide a normative framework, court practices remain inconsistent and often gender-biased, disadvantaging mothers as primary caregivers. Using a normative–empirical socio-legal approach, this research analyzes statutory regulations, Supreme Court jurisprudence, and twelve child custody decisions from Religious Courts obtained from the Supreme Court Decision Directory. No data from general courts or NGOs were used. The findings reveal three main problems: the absence of clear technical standards in custody regulations, inconsistent judicial reasoning that prioritizes fathers’ economic capacity over caregiving history, and weak enforcement of child support and post-verdict monitoring. These conditions result in limited implementation of the “best interests of the child” principle and perpetuate structural gender inequality. The study recommends legal and institutional reforms, including clearer judicial guidelines, gender-sensitive training for judges, mandatory psychosocial assessments, and stronger enforcement mechanisms for child support to ensure substantive justice for children and mothers